Discrimination, Managers, and Firm Performance: Evidence from "Aryanizations" in Nazi Germany - Kilian Huber; Volker Lindenthal; Fabian Waldinger (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Large-scale increases in discrimination can lead to dismissals of highly qualified managers. We investigate how expulsions of senior Jewish managers, due to rising discrimination in Nazi Germany, affected large corporations. Firms that lost Jewish managers experienced persistent reductions in stock prices, dividends, and returns on assets. Aggregate market value fell by roughly 1.8 percent of German GNP because of the expulsions. Managers who served as key connectors to other firms and managers who were highly educated were particularly important for firm performance. The findings imply that individual managers drive firm performance. Discrimination against qualified business leaders causes first-order economic losses.
Keywords: 330